(untitled) (CIPEEX, 2025)
Senescence results from the decline of physiological reserves and affects social, cognitive, and physical aspects. Changes in neuromuscular functions, together with deterioration of the vestibular and visual systems, reduce physical fitness and balance. Falls can be serious consequences of imbalance and represent the second leading cause of death among older adults. Thus, this study aims to identify the history of falls and dynamic balance/functional mobility in older adults. This is a cross-sectional, descriptive field study based on the analysis of 120 participants from the Open University for Older Adults at UniEVANGÉLICA (UniAPI). Functional mobility was assessed using the Timed Up and Go (TUG) test, categorizing performance into three fall risk ranges. Of the participants, 40% reported at least one fall in the last 12 months, with an average of 2.42 falls per year among frequent fallers. Analysis by age group showed that, despite longer TUG times among older adults over 75 years of age, they reported fewer falls than the 70-75 age group, suggesting the influence of multiple factors in the assessment of fall risk.